Nephrotic Syndrome a Rare Manifestation of COVID-19, a Case Report - Eskandarifar, Alireza; Abedini, Masoumeh; Aabbaspor, Saber (Journal of Pediatric Nephrology, 2020)
One of the symptoms of glomerular damage is proteinuria and nephrotic syndrome, which can be primary or secondary. Secondary nephrotic syndrome is followed by systemic diseases, malignancies, drugs, and a variety of infectious diseases. In the recent Coronavirus disease 2019 pandemic, a wide range of organ involvement has been reported, including, kidneys, cardiovascular, endocrine, and nervous systems, mostly in adults and less reported in children. Our patient was an 11-year-old child with COVID-19 who presented with diabetic ketoacidosis and developed proteinuria, nephrotic syndrome, and renal failure during the course of the disease and mild respiratory symptoms appeared at the end of the illness. Keywords: COVID-19; Corona virus disease 2019; Nephrotic Syndrome; Child.